Development of Audio-Visual Media Based on Archery ID Model in English Classroom - Putri Syukriani Tarihoran; Darmansyah; Alwen Bentri; Abna Hidayati (Universitas Islam Negeri (UIN) Syekh Wasil, Kediri, Indonesia, 2025)
Technological advances must be incorporated into the learning process. It is crucial to develop integrated learning models that incorporate learning media in the context of English language learning. This development entails the creation of an English learning model based on audiovisual content. This research aims to develop Archery's ID Model-based audiovisual media as valid, practical, and effective for teaching Procedure Text to 10th-grade vocational high school students. The proposed model is centered on utilizing audiovisual content in the form of projects. This research employs a research and development method based on the ADDIE model, encompassing the following stages: analysis, design, development, implementation, and evaluation. The data obtained from the audiovisual media trial comprises both quantitative and qualitative data. Quantitative data was collected through questionnaires distributed to test subjects. Quantitative data was also obtained from the completion of questionnaires by media validators, material validators, language validators, and students. Following the validation of the instrument by the validator, several further tests were conducted, namely a validity test, a reliability test, and an N-Gain determination.